Bacterial Calcium Transport: Energy-Dependent Calcium Uptake by Membrane Vesicles from Bacillus megaterium - Golub, Ellis E. (1974)
Membrane vesicles capable of energy-dependent calcium uptake have been prepared from Bacillus megaterium cells in log-phase growth or when undergoing sporulation. The uptake is dependent on the calcium concentration and appears saturable in vesicles from cells in log-phase growth. Both ascorbate and phenazine methosulfate are needed as a source of electrons for the energy-dependent increase in calcium uptake. Addition of 8 mM sodium cyanide inhibited the energy-dependent uptake. If this calcium uptake mechanism is a component of the sporulation-specific calcium accumulation process, the latter's functional expression would appear to be inhibited during log-phase growth.